The socioeconomic feasibility of greening rail stations: a case study in lisbon. Issue 2 (3rd April 2019) - Matos Silva, Cristina; Serro, Joana; Dinis Ferreira, Patrícia; Teotónio, Inês
Abstract: Green roofs and living walls are considered effective solutions for improving the environmental integrity of urbanized areas and the overall performance of buildings. Proposals are emerging not just for buildings but also for existing transport infrastructures that have needs/problems that can be met or addressed by such solutions. However, the economic feasibility of such sustainable solutions has not yet been clarified. This study presents a methodological approach to performing cost–benefit analyses of greening urban transport infrastructures at the separate financial, economic, and socioenvironmental levels. Infrastructure, user, and environmental dimensions are also assessed. Whole life cycle costs and socioenvironmental benefits are considered together. The methodology is applied to one of the main stations in Lisbon, Portugal: Entrecampos Railway Station. Five different case study alternatives for the station's retrofit with green infrastructures are compared to its current situation. The cost–benefit analysis demonstrated that all five greening alternatives are economically feasible. For a 50-year life cycle and a 3.36% discount rate, the net present value ranged between EUR 734, 700 and EUR 7, 733, 279. A sensitivity analysis was also performed, revealing a high degree of influence of discount and inflation rates, recreation, aesthetics improvement, well-being, and the station noise reduction on the net present value, ranging from 1.5 to 9%.